Dampak Kepercayaan Diri terhadap Prestasi Siswa Berkebutuhan Khusus Tunarungu - Sri Hidayati; Cindy Safitri; Muslimah Muslimah; Istiyati Mahmudah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2022)
Children with Special Needs (ABK) is a term used to describe children who have difficulties with the sight, hearing, or mental skills. Because they are motivated by their limitations, lots of them have poor self. There are some who say that ABK's lack of self-confidence has hurt his ability to achieve his goals. The purpose of this study is to assess how self-confidence impacts the achievement of students with special needs for the deaf. 6 deaf class students served as subjects, with just principal, 2-class teachers, and 6 parents of deaf class students participating as informants. The results reveal as many deaf students at SLBN 1 Palangka Raya had achieved academic and non-academic achievement at the provincial and national levels. They already have self-confidence in term, but different sorts of self-confidence. The findings also show that their level of confidence has an impact on their results. On the other side, their efforts have a good effect on self. This shows that ABK can succeed on a provincial and even national level, just like other regular students.